Biobank as a source of samples for determination of concentration reference ranges for cytokines, chemokines and growth factors circulating in the blood - N. N. Sushentseva; O. S. Popov; S. V. Apalko; S. P. Urazov; A. Yu. Anisenkova; A. K. Minochkin; A. S. Agafyina; S. G. Shcherbak (Кардиоваскулярная терапия и профилактика, 2022)
Aim. To determine the reference ranges of concentrations of 38 cytokines, chemokines and growth factors, as well as to measure the content of these analytes in patients with neurodegenerative and cardiovascular diseases (CVDs) using biomaterial from the biobank repository.Material and methods. The study included 303 serum and plasma samples from 281 healthy donors, 242 samples from 224 patients with neurodegenerative diseases, and 164 samples from 152 patients with CVDs from the biobank of the of St. Petersburg City Hospital № 40. In  all samples, the concentration of 38 cytokines, chemokines, and growth factors was determined by multiplex immunofluorescence assay.Results. Based on the measured concentrations in the group of healthy donors, non-parametric 95% reference ranges with 90% confidence intervals were calculated. For the majority of analytes, no sex and age differences were observed. In donors >65 years of age, the concentration of macrophage inflammatory protein-1-α was reduced and the levels of interleukin-8 and the chemokine interferon-inducible protein 10 were increased. Young donors (18-35 years) had lower levels of tumor necrosis factor-α. In groups with neurodegenerative and cardiovascular diseases, multiple deviations from the calculated reference values were found.Conclusion. Certain reference intervals are intended to evaluate the concentrations of cytokines, chemokines and growth factors determined in blood serum or plasma using Human Cytokine/Chemokine Magnetic Bead Panel 1 reagents (Merck, Millipore) on the MAGPIX system and do not imply a direct transfer to other analytical methods.